2022
DOI: 10.28991/cej-sp2021-07-013
|View full text |Cite
|
Sign up to set email alerts
|

Multi-Airport System Development Model: Case Study of Airports in Indonesia

Abstract: Indonesia's air transportation business has grown substantially to suit the community's transportation needs. An increasing number of people travel by airline each year. By way of secondary and tertiary multiplier effects, the intensifying competition between airport services provided in neighboring regions is likely to have a multiplier influence on a territory. Simultaneously, airport services that are more competitive are focused on areas with rising economic growth in sectors like tourism. MAS is an airpor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…Based on the concept of shortest-path betweenness centrality measure [58], as well as hub and spoke networks [59,60] borrowed from the domain of complex analysis, a new traffic assignment model was developed [61]. This indicated that the demand for carpooling systems was expressed as a function of various socio-demographic, land use, and environmental factors [62].…”
Section: Demand-supply Modelmentioning
confidence: 99%
“…Based on the concept of shortest-path betweenness centrality measure [58], as well as hub and spoke networks [59,60] borrowed from the domain of complex analysis, a new traffic assignment model was developed [61]. This indicated that the demand for carpooling systems was expressed as a function of various socio-demographic, land use, and environmental factors [62].…”
Section: Demand-supply Modelmentioning
confidence: 99%
“…Thus, unwanted things will not happen if the user is by existing procedures. Adisasmita & Hadipramana (2011) mentioned that transportation is an activity that has been needed by humans since ancient times until now to meet human needs. Transportation infrastructure such as planes, trains, buses, public transportation, and other vehicles are used to carry out various transportation operations.…”
Section: External Factorsmentioning
confidence: 99%
“…The escalating competition amongst airport services within a given region is likely to exert influences across other areas. Concurrently, heightened competitiveness in airport services is concentrated in regions displaying augmented economic growth, particularly in sectors such as tourism [1] In the present era, the aviation industry has increasingly turned its attention towards sustainability [2] and the pursuit of carbon emission reduction, with the aim of realizing net-zero energy buildings to enhance quality of life [3]. However, the continuous rise in passenger numbers and accompanying baggage poses challenges in the design of sustainable airports.…”
Section: Introductionmentioning
confidence: 99%